Historical aspects of arising and features of activity of startup companies: accounting and economic aspects - S.F. Legenchuk; G.V. Pilipchuk (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The history of arising and development of the concept of «startup company» have been studied and the importance of their activities have been determined. Using the largest startups (Amazon, Google, Salesforce, VMware, Facebook, Twitter, Groupon, Zynga and Аpple) the main components of their activity have been determined. Because of the lack of the scientific literature that directly investigated this topic the approaches of different authors from electronic sources have been systematized and the most used of them have been analyzed. The own vision of the definition of «startup company» and its key features have been formulated as a result of the research. The place of a startup company in the system of economic categories such as an economic activity, results of company activities, accounting, analysis and risks have been determined. The impact of the consequences of risks (positive and negative) of economic activity on the future of companies have been considered. The value of accounting and analysis for the economic activity of startup companies have been evaluated.